Parental presence in the operatory: An update. Issue 3 (December 2016) - Kisby, Lance E.
Abstract: The purpose of this paper is to present an update on the current views of dentists and parents on the controversial issue of the parent in the dental operatory. In the past, parents were excluded from the operatory because it was felt a parent would be disruptive. This position is no longer valid due to a better understanding of fear in children, a greater acceptance by dentists to have the parent present, and an increased interest of parents to be present. By understanding the evolving cultural, legal, and social elements that have contributed to changes in parenting and the family, one will find parental presence is safe and beneficial. Practical measures like following the successful pediatric medical model, where parents are routinely allowed to be present, are given to ensure success. Cooperative behavior will improve compliance which will result in effective dental treatment.